DESIGN OF A PASSING ACCURACY TEST UNDER PHYSICAL STRESS FOR ADVANCED SOCCER PLAYERS - Saher Mohammed Hameed; Imad Saad Allah Khamis (Proximus Journal Publishing, 2025)
The major goal of this research is to create a demanding field test that uses match-like physical stress conditions to assess the passing accuracy of professional football players. Fifteen players, ranging in age from eighteen to twenty-five, who had been coaching for Premier League clubs for a minimum of five years were part of the descriptive methodological research. A test was developed to guarantee a series of accurate passes to predefined objectives after subjects underwent varying degrees of physical exertion. The purpose of this test was to evaluate the candidate's passing accuracy inside a game-like simulation. We made sure the test was reliable and genuine by having a panel of professionals evaluate it. To establish reproducibility, we tested the same sample twice, each time spaced two weeks apart. The results demonstrated the reliability of the test with a statistically significant correlation coefficient. Physical pressure drastically decreases passing accuracy, according to the results, and certain places worked better than others. The research suggests that this test might be used as a realistic and objective way to evaluate passing accuracy while physically exerted. Athletes may also utilise it to monitor their technical performance as they go through training and for sports selection purposes. In future versions of the exam, researchers recommend include more realistic passing situations and comparing results across different skill levels and age groups.
Keywords: Passing accuracy; physical pressure; football